Recuperação tardia da trabeculectomia através do agulhamento comMitomicina C - Heloisa Andrade Maestrini (2009)
OBJECTIVES: To asses the efficacy and safety of needle revision with mitomycin C (MMC) in reviving failed filtering blebs during the late postoperative period, to identify factors associated with success, and to study its effect on the corneal endothelium. MATERIAL AND METHODS: This research consists of three prospective studies. The first and second studies investigated 125 eyes from 98 patients with uncontrolled glaucoma. All had at least one failed trabeculectomy, a flat filtering bleb, and a patent internal ostium on gonioscopy. Needle revision with subconjunctival injection of 8 µg of MMC was performed in the operating room, by a single surgeon, and repeated if necessary. The third paper included 42 eyes of 36 patients to study the corneal endothelium before and after needle revision. Central corneal thickness (CCT) was measured by ultrasonic pachymetry preoperatively and 1 week and 1, 3, 6, and 12 months after revision. Corneal endothelial cell density was measured with a noncontact specular microscope preoperatively and after 1, 6, and 12 months. RESULTS: Overall, 186 needling procedures were performed on 125 eyes (mean 1.49 ± 0.64 procedures per eye). Seventy-three eyes (58.4%) were needled once, 44 (35.2%) were needled twice, seven (5.6%) were needled three times, and one (0.8%) was needled four times. We reestablished aqueous flow and obtained a raised bleb in 115 eyes (92%). After an average follow-up of 20.80 ± 11.96 months, mean IOP decreased from 20.07 ± 5.20 mmHg preoperatively to 13.15 ± 6.77 mmHg (P < 0.001), and the mean number of hypotensive medications per eye decreased from 2.35 ± 1.14 at baseline to 0.78 ± 1.30 (P < 0.001) at the latest visit. The overall success rate (IOP = 16 mmHg) was 76% (58.4% without medication and 17.6% with hypotensive medications). Complications included mild hyphema (25.8%), shallow anterior chamber (18.3%), serous choroidal detachment (15.6%), bleb leakage (8.6%), and encapsulated bleb (7.5%). Most complications were minor, transient, and required no treatment. The most important variable associated with success was a lower pre-needling IOP (P < 0.001). Successful outcomes also correlated significantly with a lower IOP on the first postoperative day (P = 0.005), a longer time between trabeculectomy and needling (P = 0.030), and older age (P = 0.050; borderline significance). The success rates tended to be greater in whites, pseudophakic eyes, and in eyes with a previous fornix-based trabeculectomy. There was no statistically significant difference between preoperative and postoperative CCT and endothelialcell density during the first year of follow-up. CONCLUSIONS: Needle revision with adjunctive MMC is effective for reviving flat filtering blebs and controlling IOP, even several years after the original trabeculectomy, and seems to be safe for the corneal endothelium. Complications were minor and transient. Higher success rates were achieved in eyes with lowerpre-needling IOP, lower IOP on the first postoperative day, longer interval between trabeculectomy and needling, and in older patients.